Study of Drinking Water Supply System Development Planning in Dusun Tuti, North Lombok Regency,Â Indonesia - Ari Ramadhan Hidayat; Muhammad Khalis Ilmi (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
Dusun Tuti is part of the administrative area of ​​Sokong Village, Tanjung District, North Lombok Regency. Tuti Hamlet has a population of 596 people spread across 5 (five) RT. Currently, meeting the need for clean water in Tuti Hamlet uses several drilled wells that are still functioning. In total there are 5 locations for drilled wells. However, currently only 2 drilled wells can operate and are unable to serve the amount of clean water needed in Tuti Hamlet. This is due to the absence of an adequate drinking water supply system network to distribute water originating from several drilled wells that are still operating. Therefore, it is necessary to plan the development of a drinking water supply system (SPAM) in Tuti Hamlet to overcome this problem. The aim of this research is to calculate the projected clean water needs in Tuti Hamlet for the next 15 years and plan the clean water piping network so that the clean water needs of the Tuti Hamlet community can be met. Population projections to determine the projected need for clean water using arithmetic methods. The population projection results show that the population in 2038 will be 920 people with an average need for clean water of 0.11 liters/second. The main distribution network system development plan in 2022-2038 uses 2 inch diameter PVC pipes for 450 m, 1.5 inch diameter PVC pipes for 3000 m and 0.5 inch diameter PVC pipes for 3600 m.